Characterization of dominant lactic acid bacteria isolated from São Jorge cheese, using biochemical and ribotyping methods - Kongo, J.M; Ho, A.J; Malcata, F.X; Wiedmann, M (Journal of applied microbiology, 2007)
To identify, using phenotypic and genotypic methods, the dominant lactic acid bacteria (LAB) present in São Jorge cheese - one of the 11 Portuguese cheeses currently bearing an Appéllation d'Origine Protegée status. A total of 225 isolates from milk, curd and cheeses throughout ripening were identified to the genus level, 108 to the species level and ten to the strain level. Phenotypic methods indicated that lactobacilli, followed by enterococci, were the dominant bacteria. The most frequently isolated species were Lactobacillus paracasei, Lactobacillus rhamnosus, Enterococcus faecalis and Enterococcus faecium. Ribotyping differentiated three L. paracasei, two E. faecalis and one Lactobacillus plantarum types. Enterococcus spp. exhibited the highest esterase and β-galactosidase activities among all isolates. The dominant LAB in São Jorge cheese are L. paracasei, L. rhamnosus, E. faecalis and E. faecium. Enterococcus likely plays a leading role upon acidification and aroma development in said cheese. Our results support that a combination of conventional biochemical methods with genotypic methods allows for a thorough characterization and identification of isolates. Despite the limited number of isolates subject to molecular subtyping, a few specific Enterococcus and Lactobacillus strains were found that are promising ones for development of a starter culture. Hence, L. paracasei and E. faecalis are good candidates for a tentative starter culture, designed for manufacturing of São Jorge cheese at large - which takes advantage of actual isolates, in attempts to eventually standardize the quality of said cheese variety.